Piper hapnium : A rare Piper species from Peruvannamuzhi, Kerala - A new report - S Biju, K V Saji, B Sasikumar, K Johnson George, (Journal of Spices and Aromatic Crops, 2001)
Piper hapnium is considered to be an endangered species of Piper. Occurrence of this species is reported mainly from the low-lying hills of Western Ghats. Though, scientists of Indian Institute of Spices Research conducted extensive surveys for collection of Piper species from the Western Ghats, P. hapnium (female plants) could be collected only once from the low land hills of Courtallum, Tamil Nadu. Earlier surveys conducted in the Silent Valley forests of Western Ghats (Ravindran et al. 1990) revealed the non-occurrence of P. hapnium in this area, though this sanctuary is identified as one of the rich centers for Piper diversity.